2017
DOI: 10.14814/phy2.13372
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular and ventilatory responses to acute normobaric hypoxia in girls and women

Abstract: Physiological responses to hypoxia in children are incompletely understood. We aimed to characterize cerebrovascular and ventilatory responses to normobaric hypoxia in girls and women. Ten healthy girls (9.9 ± 1.7 years; mean ± SD; Tanner stage 1 and 2) and their mothers (43.9 ± 3.5 years) participated. Internal carotid (ICA) and vertebral artery (VA) velocity, diameter and flow (Duplex ultrasound) was recorded pre‐ and post‐1 h of hypoxic exposure (FIO 2 = 0.126;~4000 m) in a normobaric chamber. Ventilation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
9
7
0
Order By: Relevance
“…When assessed bilaterally, acute poikilocapnic hypoxia caused the same vasodilatation (ICAs 6.9 (3.7) vs. VAs 7.0 (3.8)%; P = 0.87) and comparable relative increases in blood flow and blood flow reactivity in the ICAs and VAs (Figure 2f,h). These regional blood flow responses to acute hypoxia are similar to those previously reported from studies employing the typical method of doubling unilateral measurements (Lewis et al., 2014; Morris et al., 2017; Willie et al., 2012). There are as many studies reporting that the increase in blood flow to hypoxia is mediated by vasodilatation in both ICAs and VAs to extreme (<80% SnormalpO2) poikilocapnic hypoxia (Lewis et al., 2014; Morris et al., 2017) or isocapnic hypoxia (Fernandes et al., 2018; Hoiland et al., 2017) as there are reporting no vasodilatation (Lafave et al., 2019; Ogoh et al., 2013; Willie et al., 2012; Willie, Smith, et al., 2014), with others suggesting regionally specific vasodilatation (Kellawan et al., 2017; Subudhi et al., 2014).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…When assessed bilaterally, acute poikilocapnic hypoxia caused the same vasodilatation (ICAs 6.9 (3.7) vs. VAs 7.0 (3.8)%; P = 0.87) and comparable relative increases in blood flow and blood flow reactivity in the ICAs and VAs (Figure 2f,h). These regional blood flow responses to acute hypoxia are similar to those previously reported from studies employing the typical method of doubling unilateral measurements (Lewis et al., 2014; Morris et al., 2017; Willie et al., 2012). There are as many studies reporting that the increase in blood flow to hypoxia is mediated by vasodilatation in both ICAs and VAs to extreme (<80% SnormalpO2) poikilocapnic hypoxia (Lewis et al., 2014; Morris et al., 2017) or isocapnic hypoxia (Fernandes et al., 2018; Hoiland et al., 2017) as there are reporting no vasodilatation (Lafave et al., 2019; Ogoh et al., 2013; Willie et al., 2012; Willie, Smith, et al., 2014), with others suggesting regionally specific vasodilatation (Kellawan et al., 2017; Subudhi et al., 2014).…”
Section: Discussionsupporting
confidence: 87%
“…When assessed bilaterally, acute poikilocapnic hypoxia caused the same vasodilatation (ICAs 6.9 (3.7) vs. VAs 7.0 (3.8)%; P = 0.87) and comparable relative increases in blood flow and blood flow reactivity in the ICAs and VAs (Figure 2f,h). These regional blood flow responses to acute hypoxia are similar to those previously reported from studies employing the typical method of doubling unilateral measurements (Lewis et al, 2014;Morris et al, 2017;Willie et al, 2012). There are as many studies reporting that the increase in blood flow to hypoxia is mediated by vasodilatation in both ICAs and VAs to extreme (<80%…”
Section: Bilateral Extracranial Blood Flow Regulation To Hypoxiasupporting
confidence: 85%
See 1 more Smart Citation
“…3c-d). Unlike the lateral resolution, the axial resolution of the UFF-PAM system is determined by the detected ultrasound bandwidth [32], which is ~33 µm across the scanning range. For in vivo experiments, we usually reduce the volumetric frame rate to 0.3 Hz, with a PRR of 800 kHz, a 2D frame rate of 1 kHz, and a scanning step size of 15-19 μm.…”
Section: Resultsmentioning
confidence: 99%
“…A substantial increase in the ICA diameter with age has been reported in children, with larger ICA diameter in 10-19 year old youth compared to 4-9 year old children (33). In contrast, Morris et al (34) found girls (9.9  1.7 years) and women (43.9  3.5 years) had similar sized ICA diameter and vertebral artery (VA) diameter. Global CBF also increases with age up until about 8-10 years, then decreases through adolescence to adult values (35).…”
Section: Age Maturation and Cerebrovascular Developmentmentioning
confidence: 98%